Improving Social Management Performance Based on Professional Managerial Roles (by the Example of the MBA Program’s Students) - Svetlana Vyacheslavovna Smeltsova (Управленческое консультирование)
Тhis article is the result of the author’s empirical sociological research students of the MBA program that demonstrates theoretical, applied and practical aspects of improving social management performance based on professional managerial roles.